2002
DOI: 10.1073/pnas.232693499
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of neuronal calcium sensor-1 (NCS-1) in the prefrontal cortex of schizophrenic and bipolar patients

Abstract: The delineation of dopamine dysfunction in the mentally ill has been a long-standing quest of biological psychiatry. The present study focuses on a recently recognized group of dopamine receptor-interacting proteins as possible novel sites of dysfunction in schizophrenic and bipolar patients. We demonstrate that the dorsolateral prefrontal cortex in schizophrenia and bipolar cases from the Stanley Foundation Neuropathology Consortium display significantly elevated levels of the D2 dopamine receptor desensitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 61 publications
6
143
1
Order By: Relevance
“…It is suggested that alterations in the DA system in the brain of schizophrenics occurs during development and may not be due to secondary effects of drug treatment (Albert et al, 2002;Koh et al, 2003;Souza et al, 2008Souza et al, , 2010. The main target for antipsychotics, the DA receptor D 2 , modulates the Akt pathway in mammals (Lai et al, 2006;Beaulieu et al, 2007;Tan et al, 2008), and our data show that this effect is conserved in zebrafish.…”
Section: Discussionsupporting
confidence: 51%
“…It is suggested that alterations in the DA system in the brain of schizophrenics occurs during development and may not be due to secondary effects of drug treatment (Albert et al, 2002;Koh et al, 2003;Souza et al, 2008Souza et al, , 2010. The main target for antipsychotics, the DA receptor D 2 , modulates the Akt pathway in mammals (Lai et al, 2006;Beaulieu et al, 2007;Tan et al, 2008), and our data show that this effect is conserved in zebrafish.…”
Section: Discussionsupporting
confidence: 51%
“…With regard to the Ins(1,4,5) P 3 /Ca 2+ pathway, there are a number of observations indicating that the resting and activated levels of Ca 2+ are elevated in BD. 30 The neuronal Ca 2+ sensor-1 (NCS-1), which is known to be elevated in the prefrontal cortex in both BD and schizophrenia, 34 is known to enhance the activity of the Ins(1,4,5)P 3 Rs 35 and this would contribute to an increase in the intracellular level of Ca 2+ . Increase NCS-1 activity may also influence membrane excitability by desensitizing the D2 receptors.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…NCS-1 has also been linked to serious neurodegenerative disorders including schizophrenia, bipolar disorder (BD) (32), and autism (33,34). However, the dysfunctions of NCS-1 are poorly characterized on the molecular level, and whether they involve altered functional profiles or loss of function due to formation of misfolded states is currently unknown.…”
Section: Significancementioning
confidence: 99%